2016
DOI: 10.1093/glycob/cww065
|View full text |Cite
|
Sign up to set email alerts
|

Interactions of mucins with the Tn or Sialyl Tn cancer antigens including MUC1 are due to GalNAc–GalNAc interactions

Abstract: The molecular mechanism(s) underlying the enhanced self-interactions of mucins possessing the Tn (GalNAcα1-Ser/Thr) or STn (NeuNAcα2-6GalNAcα1-Ser/Thr) cancer markers were investigated using optical tweezers (OT). The mucins examined included modified porcine submaxillary mucin containing the Tn epitope (Tn-PSM), ovine submaxillary mucin with the STn epitope (STn-OSM), and recombinant MUC1 analogs with either the Tn and STn epitope. OT experiments in which the mucins were immobilized onto polystyrene beads rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(23 citation statements)
references
References 62 publications
2
21
0
Order By: Relevance
“…Cohen and Varki argue that “ it is likely that glycan microdomains are mostly stabilized by carbohydrate–carbohydrate interactions, which are too weak to withstand the standard biochemical methods used to study protein–protein interactions (e.g., immunoprecipitation). ” The later evidence for the ability of mucins of varying glycosylation pattern to form interactions, as provided using both AFM [ 152 , 153 ] and OT [ 154 ], strengthens this hypothesis.…”
Section: Mechanisms Of Glycan-based Adhesion Of Bacteriamentioning
confidence: 88%
See 2 more Smart Citations
“…Cohen and Varki argue that “ it is likely that glycan microdomains are mostly stabilized by carbohydrate–carbohydrate interactions, which are too weak to withstand the standard biochemical methods used to study protein–protein interactions (e.g., immunoprecipitation). ” The later evidence for the ability of mucins of varying glycosylation pattern to form interactions, as provided using both AFM [ 152 , 153 ] and OT [ 154 ], strengthens this hypothesis.…”
Section: Mechanisms Of Glycan-based Adhesion Of Bacteriamentioning
confidence: 88%
“…To date, only one example shows the utility of this technique to measure glycan-glycan interactions. In 2016, Haugstad et al showed that OT could be used to measure the adhesion forces between self-associating mucins presenting particular glycan structures [ 154 ]. The experimental data provided in the paper ( Figure 4 b) allowed the authors to conclude that a particular glycan structure, the N -acetylgalactosamine (GalNAc), was responsible for the self-interactions observed for the mucins.…”
Section: Mechanisms Of Glycan-based Adhesion Of Bacteriamentioning
confidence: 99%
See 1 more Smart Citation
“…However, sTn antigen may promote tumor cells to migrate and invade underlying tissue, and eventually reach blood or lymph vessels . All the evidences mentioned above suggest that sTn antigen plays a transient role in the progression of cancer .…”
Section: Relationship Between Stn Antigen and Tumor Cellsmentioning
confidence: 99%
“…To put this mode of binding in context, and accepting that there will be variations between experimental conditions, the average binding affinity of L. mexicana nectomonad LPG for GalNAc is comparable to other protein-glycan interactions between bacterial pili and mucins; 43,44 bacterial pili and host pneumocytes; 45 bacterial adhesins; [46][47][48] and soybean agglutinin and porcine gastric mucin, 49 and greater than a range of glycan-glycan interactions recorded within selfassembling mucins. [50][51][52] Sample force curves showing extension and rupture of single and multiple bonds between functionalized AFM tips and a strongly adhesive WT L. mexicana nectomonad promastigote are shown in Fig. 4c and d, respectively.…”
Section: Force-distance Curvesmentioning
confidence: 99%